Pengaruh permainan tradisional gobak sodor dan tradisional gobak bunder terhadap peningkatan kebugaran jasmani pada siswa kelas IX MTS bahrul ulum NW telage bagek - Muh Zainul Ilham S; Mujriah; Adi Suriatno (Jurnal Pengetahuan dan Pendidikan, 2024)
The aim of this research is to determine the effect of the traditional games Gobak Sodor and Gobak Bunder on improving the physical fitness of grade IX students at MTs Bahrul Ulum NW Telage Bagek. The method used in this research is quasi-experimental. The subjects in this study were 15 grade IX students who were given the traditional games Gobak Sodor and Gobak Bunder for 2 months with a frequency of 3 sessions per week for each game. Data collection was carried out through testing, using the TKJI (Indonesian Physical Fitness Test) instrument for the 13-15 age group. After 2 months, there was a significant effect of the traditional games Gobak Sodor and Gobak Bunder on improving physical fitness, with paired t-test results showing a value of 0.001 < 0.05. This indicates that the traditional games Gobak Sodor and Gobak Bunder have a significant influence on increasing physical fitness. In conclusion, there is an effect of the traditional games Gobak Sodor and Gobak Bunder on the physical fitness improvement of grade IX students at MTs Bahrul Ulum NW Telage Bagek.